The UPeXplorer a three-dimensional map of the UP Diliman campus which integrates the global communications capability of the internet and the interactive environment of virtual reality using VRML - Laconsay, Rommel U.; Novilla, Francisco III A.; Ong, Airyn Mary B.; Rivera, Teddy D. (1997)
For centuries, man had always thought of ways of communicating effectively. As we occupied more space and became more scattered, verbal face-to-face communication wasn't just enough This had led man to invent writing as another means of communication. The inventions and development of the telephone, radio, television and other media were also manifestations of our desire to effectively express our ideas and acquire information from others.

The advent of computers revolutionized mass communication and information technology. It increased our demand for information tremendously. It gave us new methods of communication that were impossible to achieve in the past few years. But current methods of information retrieval and representation using computers are far from man's natural way of acquiring information, that is by looking, hearing, moving and utilizing our other senses to fully understand others and the environment. Yes, we can read texts generated by the computer, but isn't it much better if we can actually hear, feel and experience what the text is trying to say? It is also true that we can see pictures of buildings and places on the computer screen but we cannot manipulate these images for us to see what is behind those buildings. Thus, our goal is to find and implement better ways or communication, information retrieval and representation using computers. methods of We think that by creating a virtual representation of the University of the Philippines Diliman Campus, we can provide a sample implementation of this new method.

This virtual image of the UP Diliman Campus is a three-dimensional virtual world on the computer monitor which will not only allow us to view and visit the campus but will also provide us with some services that are currently offered in the campus. Aside from helping us locate a building in a short time and determining whether offices or libraries are closed or not, without physically going to those places (saving time, effort, and money), we can also get information from different colleges in an instant. This could be done effortlessly in a little amount of time. Since the virtual image would be available in the internet, anyone can actually visit UP and have an idea of what it looks like (virtually) It is our hope that through this project we can best achieve our goals of effective communication."
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: VRML (Computer program language); Cartography -- Data processing; Digital mapping; UPeXplorer